Condition Assessment of the Cable Trench Based on an Intelligent Inspection Robot - Jia, Zhiwei; Tian, Yihong; Liu, Zheng; Fan, Shaosheng (Frontiers in Energy Research, 2022)
Accurate evaluation of cable trench condition is the key to realizing its intelligent operation and maintenance, and the intelligent cable trench inspection robot is a reliable information acquisition method for the condition assessment of cable trench. According to the task requirements and site environment, an intelligent inspection robot is designed. Crawler-type motion mechanism is determined by demands of sizes and obstacle-surmounting. Cartographer SLAM technology is used to map the underground cable trench environment, and a path planning method combined improved A* algorithm and dynamic window method (DWA) is presented. Multiple sensors are equipped on this robot and various information is obtained. Based on the information above, a condition assessment method of underground cable trench is proposed. An extension neural network model is constructed to assess air quality. Channel capacity and ground flatness are calculated to evaluate the internal structure of the cable trench. Water depth and water surface area are comprehensively used to evaluate the hazard of water accumulation. The evaluation results are used to realize the linkage control of the cable trench operation and maintenance. Field test shows that the intelligent inspection robot can reliably obtain 7 kinds of information from underground cable trench, and the proposed condition evaluation method can assess the condition of the cable trench and provides 4 kinds of suggestions for potential hazards and hazards.